2(x+6)+82=9x-7(x+2)

Simple and best practice solution for 2(x+6)+82=9x-7(x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+6)+82=9x-7(x+2) equation:


Simplifying
2(x + 6) + 82 = 9x + -7(x + 2)

Reorder the terms:
2(6 + x) + 82 = 9x + -7(x + 2)
(6 * 2 + x * 2) + 82 = 9x + -7(x + 2)
(12 + 2x) + 82 = 9x + -7(x + 2)

Reorder the terms:
12 + 82 + 2x = 9x + -7(x + 2)

Combine like terms: 12 + 82 = 94
94 + 2x = 9x + -7(x + 2)

Reorder the terms:
94 + 2x = 9x + -7(2 + x)
94 + 2x = 9x + (2 * -7 + x * -7)
94 + 2x = 9x + (-14 + -7x)

Reorder the terms:
94 + 2x = -14 + 9x + -7x

Combine like terms: 9x + -7x = 2x
94 + 2x = -14 + 2x

Add '-2x' to each side of the equation.
94 + 2x + -2x = -14 + 2x + -2x

Combine like terms: 2x + -2x = 0
94 + 0 = -14 + 2x + -2x
94 = -14 + 2x + -2x

Combine like terms: 2x + -2x = 0
94 = -14 + 0
94 = -14

Solving
94 = -14

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5w^2-15w+12=2 | | -4x+3(3x-4)=1-8x | | 42-(3y+2)=2(y+2)+4y | | -2t^2-3t+9=0 | | 35x-10=23x+5 | | 7y+2y=-38-11 | | 6x-3=16x+33 | | -3y+7=-5+4y | | 81c^2-36c+4= | | -88=10x+2 | | (2x+1)+(x-1)= | | -2a+3+3a=13-27 | | 16r^2=36+36r | | 8s^2=12+20s | | x+298=18 | | 6x^5-12x^3+6x=0 | | 8s+6t-(-5s)-2t= | | 4x+12=11+3x | | 2(3x-1)=-3(4-2x) | | 5(w-7)=w+4(w+1) | | 5+x=-2x+14 | | y+[-16]=-12 | | -0.25x+0.5-4= | | 4y+7y=15+y | | x^4+x^3-6x^2-14x+12=0 | | 6w^2=16+20w | | 7mn-6m-mn+2mn-4np+2= | | 9c^3+15c^2-36c= | | X-2=2x-7 | | -2-7+9+-5(-1)=-11 | | -6=4+4t-2t+16 | | 8c^2=18+18c |

Equations solver categories